Stellate Ganglion Block Used to Treat Symptoms Associated With Combat-Related Post-Traumatic Stress Disorder: A Case Series of 166 Patients. Issue 10 (1st October 2014) - Mulvaney, Sean W.; Lynch, James H.; Hickey, Matthew J.; Rahman-Rawlins, Tabassum; Schroeder, Matthew; Kane, Shawn; Lipov, Eugene
ABSTRACT: Objective: Report the successful use of stellate ganglion blocks (SGBs) in 166 active duty service members with multiple combat deployments experiencing anxiety symptoms associated with post-traumatic stress disorder (PTSD). Background: Successful treatment of PTSD symptoms with SGB has been reported previously. This is the largest published case series evaluating SGB with a minimum of 3 months follow-up. Methods: Following clinical interview including administration of the PTSD Checklist (PCL), 166 service members with symptoms of PTSD elected to receive a SGB. All patients received a SGB on the right side at the level of the sixth cervical vertebrae (C6). The PCL was administered the day before treatment to establish a baseline, repeated 1 week later, and then monthly out to 3 months. A positive response was considered to be an improvement in the PCL score by 10 or greater points. Follow-up PCL scores from 3 to 6 months were obtained and analyzed for 166 patients. Results: In a military population with multiple combat deployments, over 70% of the patients treated had a clinically significant improvement in their PCL score which persisted beyond 3 to 6 months postprocedure. Conclusion: Selective blockade of the right cervical sympathetic chain at the C6 level is a safe and minimally invasive procedure that may provide durable relief from anxiety symptoms associated with PTSD.